2010
DOI: 10.1007/s00239-010-9393-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Marine Mussels (Mytilus spp.) Gender Associated mtDNA: Rapidly Evolving atp8

Abstract: The unusual mode of mitochondrial DNA inheritance, with two separate: maternal (F) and paternal (M) lineages, gives unique opportunities to study the evolution of the mitochondrial genome. This system was first discovered in the marine mussels Mytilus. The three related species: Mytilus edulis, Mytilus galloprovincialis and Mytilus trossulus form a complex in which the divergence of M and F lineages pre-dates the speciation. The complete mitochondrial genomes of both lineages were known for all species except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 91 publications
6
54
0
Order By: Relevance
“…Among the animal groups that have been sampled, atp8 has been independently lost from the mtDNA genomes in some bivalve molluscs (Ren et al, 2010) but is found in others (e.g. in Mytilus see (Breton et al, 2010); (Smietanka et al, 2010)), secernentean nematodes (Lavrov and Brown, 2001), and platyhelminths (Le et al, 2000)). All 5 species of chaetognaths studied so far have also lost both their atp6 and 8 genes (Faure and Casanova, 2006; Helfenbein et al, 2004; Miyamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the animal groups that have been sampled, atp8 has been independently lost from the mtDNA genomes in some bivalve molluscs (Ren et al, 2010) but is found in others (e.g. in Mytilus see (Breton et al, 2010); (Smietanka et al, 2010)), secernentean nematodes (Lavrov and Brown, 2001), and platyhelminths (Le et al, 2000)). All 5 species of chaetognaths studied so far have also lost both their atp6 and 8 genes (Faure and Casanova, 2006; Helfenbein et al, 2004; Miyamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic studies about the evolutionary relationships among Mytilus spp. have suggested that Southern Hemisphere mussels could be closely related to those mussels in the M. edulis complex of the Northern Hemisphere in which M. edulis and M. galloprovincialis are sister taxa, whereas M. trossulus is more distantly related518212223.…”
mentioning
confidence: 99%
“…Other than the structural uncertainty, this genome is reasonably complete, with the possible exception of atp8. This is not surprising given the difficulties associated with detection of this gene (Breton et al, 2010;Ś mietanka et al, 2010). The possibility that one of the anonymous ORFs is in fact encoding atp8 cannot be dismissed; however, there is also no positive argument supporting such a claim.…”
Section: Discussionmentioning
confidence: 99%